PENGARUH SELF-REGULATED LEARNING TERHADAP MOTIVASI BELAJAR SISWA - Siti Aimah; Muhimatul Ifadah (Universitas Muhammadiyah Semarang, 2014)
This study aimed to find out the students’ motivation in learning through self-regulated learning. In-depth the research was done to know whether or not self-regulated learning (SRL) influenced the students’ motivation in learning. The research was conducted to the second semester students of English Department who took Intermediate Reading Comprehension in the academic year of 2013/2014. In achieving the purpose of the research, a classroom action research was conducted which consisted of two cycles. Each cycle of the research was planning, action, observation, and reflection. The result showed that SRL influenced the motivation of the students to find out their own way in learning and comprehending the materials got actively and autonomously. The students felt that SRL helped them in getting more comfortable and confidence when they had to convey their feeling, and thought to the others.